Renal Inflammation and Fibrosis: A Double-edged Sword. (September 2019) - Black, Laurence M.; Lever, Jeremie M.; Agarwal, Anupam
Renal tissue injury initiates inflammatory and fibrotic processes that occur to promote regeneration and repair. After renal injury, damaged tissue releases cytokines and chemokines, which stimulate activation and infiltration of inflammatory cells to the kidney. Normal tissue repair processes occur simultaneously with activation of myofibroblasts, collagen deposition, and wound healing responses; however, prolonged activation of pro-inflammatory and pro-fibrotic cell types causes excess extracellular matrix deposition. This review focuses on the physiological and pathophysiological roles of specialized cell types, cytokines/chemokines, and growth factors, and their implications in recovery or exacerbation of acute kidney injury.